Dual angiotensin receptor and neprilysin inhibition as an alternative to angiotensin‐converting enzyme inhibition in patients with chronic systolic heart failure: rationale for and design of the Prospective comparison of ARNI with ACEI to Determine Impact on Global Mortality and morbidity in Heart Failure trial (PARADIGM‐HF). (September 2013) - McMurray, John J. V.; Packer, Milton; Desai, Akshay S.; Gong, Jim; Lefkowitz, Martin P.; Rizkala, Adel R.; Rouleau, Jean; Shi, Victor C.; Solomon, Scott D.; Swedberg, Karl; Zile, Michael R.; ,
<x xml:space="preserve">Abstract</x> Aims Although the focus of therapeutic intervention has been on neurohormonal pathways thought to be harmful in heart failure (HF), such as the renin–angiotensin–aldosterone system (RAAS), potentially beneficial counter‐regulatory systems are also active in HF. These promote vasodilatation and natriuresis, inhibit abnormal growth, suppress the RAAS and sympathetic nervous system, and augment parasympathetic activity. The best understood of these mediators are the natriuretic peptides which are metabolized by the enzyme neprilysin. LCZ696 belongs to a new class of drugs, the angiotensin receptor neprilysin inhibitors (ARNIs), which both block the RAAS and augment natriuretic peptides. Methods Patients with chronic HF, NYHA class II–IV symptoms, an elevated plasma BNP or NT‐proBNP level, and an LVEF of ≤40% were enrolled in the Prospective comparison of ARNI with ACEI to Determine Impact on Global Mortailty and morbidity in Heart Failure trial (PARADIGM‐HF). Patients entered a single‐blind enalapril run‐in period (titrated to 10 mg b.i.d.), followed by an LCZ696 run‐in period (100 mg titrated to 200 mg b.i.d.). A total of 8436 patients tolerating both periods were randomized 1:1 to either enalapril 10 mg b.i.d. or LCZ696 200 mg b.i.d. The primary outcome is the composite of cardiovascular death or HF hospitalization, although the trial is powered to detect a 15% relative risk reduction in cardiovascular death. Perspectives PARADIGM‐HF will determine the place of the ARNI LCZ696 as an alternative to enalapril in patients with systolic HF. PARADIGM‐HF may change our approach to neurohormonal modulation in HF. Trial registration NCT01035255